Expression and Localization Profiles of Rhoptry Proteins in Plasmodium berghei Sporozoites - Tokunaga, Naohito; Nozaki, Mamoru; Tachibana, Mayumi; Baba, Minami; Matsuoka, Kazuhiro; Tsuboi, Takafumi; Torii, Motomi; Ishino, Tomoko (Frontiers in Cellular and Infection Microbiology, 2019)
In the Plasmodium lifecycle two infectious stages of parasites, merozoites, and sporozoites, efficiently infect mammalian host cells, erythrocytes, and hepatocytes, respectively. The apical structure of merozoites and sporozoites contains rhoptry and microneme secretory organelles, which are conserved with other infective forms of apicomplexan parasites. During merozoite invasion of erythrocytes, some rhoptry proteins are secreted to form a tight junction between the parasite and target cell, while others are discharged to maintain subsequent infection inside the parasitophorous vacuole. It has been questioned whether the invasion mechanisms mediated by rhoptry proteins are also involved in sporozoite invasion of two distinct target cells, mosquito salivary glands and mammalian hepatocytes. Recently we demonstrated that rhoptry neck protein 2 (RON2), which is crucial for tight junction formation in merozoites, is also important for sporozoite invasion of both target cells. With the aim of comprehensively describing the mechanisms of sporozoite invasion, the expression and localization profiles of rhoptry proteins were investigated in Plasmodium berghei sporozoites. Of 12 genes representing merozoite rhoptry molecules, nine are transcribed in oocyst-derived sporozoites at a similar or higher level compared to those in blood-stage schizonts. Immuno-electron microscopy demonstrates that eight proteins, namely RON2, RON4, RON5, ASP/RON1, RALP1, RON3, RAP1, and RAMA, localize to rhoptries in sporozoites. It is noteworthy that most rhoptry neck proteins in merozoites are localized throughout rhoptries in sporozoites. This study demonstrates that most rhoptry proteins, except components of the high-molecular mass rhoptry protein complex, are commonly expressed in merozoites and sporozoites in Plasmodium spp., which suggests that components of the invasion mechanisms are basically conserved between infective forms independently of their target cells. Combined with sporozoite-stage specific gene silencing strategies, the contribution of rhoptry proteins in invasion mechanisms can be described.